No Tillage Increases SOM in Labile Fraction but Not Stable Fraction of Andosols from a Long-Term Experiment in Japan - Jeannette Aduhene-Chinbuah; Soh Sugihara; Masakazu Komatsuzaki; Tomoyasu Nishizawa; Haruo Tanaka (Agronomy, 2022)
No tillage (NT) fosters carbon (C) sequestration, increases soil organic matter (SOM) stock, and improves soil health. However, its effect on SOM accumulation in Andosol, which has high OM stabilization characteristics due to its specific mineral properties, remains unclear. In this study, we evaluated the effect of NT on SOM content and its distribution by the physical fractionation method and assessed the quality of accumulated SOM in each fraction. We collected soil samples at 0–2.5, 2.5–7.5, and 7.5–15 cm depths from NT and conventional tillage (CT) plots in a long-term (19 years) field experiment of Andosols in Ibaraki, Japan. The soil samples were separated into light fraction (LF), coarse-POM (cPOM: 0.25–2 mm), fine-POM (fPOM: 0.053–0.25 mm), and silt + clay (mOM: <0.053 mm). The C, nitrogen (N), and organic phosphorus (Po) contents of each fraction were analyzed. The C content of cPOM and fPOM in NT at 0–7.5 cm was higher than in CT, while there was no clear difference in the mOM fraction or deeper layer (7.5–15 cm). NT increased the C, N, and Po contents in the labile POM fractions at the surface layers but did not increase the stable fraction or change the quality.